Pharmacokinetic Profile of A New Diclofenac Prodrug without Gastroulcerogenic Effect - de Campos, Michel Leandro [UNESP]; Baldan-Cimatti, Helen Mariana [UNESP]; Davanço, Marcelo Gomes [UNESP]; Nogueira, Marco Antônio Ferraz [UNESP]; Padilha, Elias Carvalho [UNESP]; Candido, Caroline Damico [UNESP]; dos Santos, Jean Leandro [UNESP]; Peccinini, Rosangela Goncalves [UNESP] (My University, 2013)
Gastrotoxicity is a major problem for long-term therapy with non-steroidal anti-inflammatory drugs (NSAIDs). DICCIC (1-(2,6-dichlorophenyl)indolin-2-one) is a new diclofenac prodrug, which has proven anti-inflammatory activity without gastroulcerogenic effect. The aim of this work was to compare the pharmacokinetic profiles of diclofenac from DICCIC (7.6 mg/kg equivalent to 8.1 mg/kg diclofenac) and diclofenac (8.1 mg/kg) administration in Wistar rats weighing 250-300 g (n=20). The doses were calculated by interspecific allometric scaling based on the 2 mg/kg from diary human dose of diclofenac. Blood samples were collected in heparinized tubes via the femoral artery through the implanted catheter. The plasma was separated and quantitation was made in a HPLC system with a UV-Vis detector. The confidence limits of the bioanalytical method were appropriate for its application in a preclinical pharmacokinetic study. The AUC of diclofenac from DICCIC (53.7± 5.8 ug/mL.min) was significantly less (Mann Whitney test, p<0.05) than that of diclofenac from diclofenac administration (885.9 ± 124,8 ug/mL.min). Terminal half-life of diclofenac from DICCIC (50.1 ± 17.2 min) was significantly less (Mann Whitney test, p<0.05) than that of diclofenac from diclofenac administration (247.4 ± 100.9 min). Still the parameters clearance and distribution volume were calculated for diclofenac from diclofenac, whose results were 9.2 ±1.2 mL/min.kg and 3.3 ±1.2 L/kg, respectively. The results of DICCIC from DICCIC administration were 108.9 ± 19.6 mL/min.kg and 7.8 ± 2.4 L/kg for clearance and distribution volume, respectively. The pharmacokinetic profile demonstrated that there was an increase in diclofenac elimination and a lower exposure to diclofenac with administration of DICCIC compared to diclofenac. © 2013 Bentham Science Publishers.
Keywords: 1-(2,6-dichlorophenyl)indolin-2-one; Bioanalytical method; Diclofenac prodrug; Preclinical pharmacokinetic profile; [1 (2,6 dichlorophenyl)indolin 2 one]; diclofenac; diclofenac derivative; prodrug; unclassified drug; allometry; animal experiment; area under the curve; controlled study; distribution volume; drug clearance; drug determination; drug distribution; drug elimination; drug exposure; drug half life; high performance liquid chromatography; limit of quantitation; male; nonhuman; pharmaceutical equivalence; plasma concentration-time curve; priority journal; rat